Manajemen Kaderisasi Guru Al Qur’an di Madrasah Aliyah Al Urwatul Wutsqo Bulurejo Diwek Jombang - Solechan Solechan (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
The Qur'an is a guide for every human being, including the Muslim population in Indonesia. However, not a few people who do not understand the Qur'an. The contributing factor is the number of teachers of the Qur'an that is not comparable with the number of Muslim population in Indonesia. The solution, needs a breakthrough in the field of procurement of Qur'an teachers in large numbers. The process can be pursued through the Qur'an teacher regeneration program. MA-UW is an educational institution, among the programs that are launched is the regeneration of the Qur'an teacher. This research focuses on three aspects, namely: Planning the regeneration of the Qur'an teacher in MA-UW (2) Implementation of the regeneration of the Qur'an teacher in MA-UW? (3) Evaluation of the regeneration of the Qur'an teacher in MA-UW? To solve problems and find answers to the three problems above, this study uses a qualitative approach with asingle case study approach. The results of this study found that: 1. Planning the regeneration of the Qur'an teacher at MA al Urwatul Wutsqo: a. Prepare books as a reference for regeneration material b. Prepare students to be recruited c. Formation of teaching practice groups d. Providing teaching places at the elementary / junior high school level and MI / MTs level. 2. Implementation of regeneration: a. Cadre implementation starts from class 1 (one). b. Cadre implementation is carried out during school hours. c. Granting trainer certificates for those who have graduated. d. Teaching practice in elementary / junior high and MI / MTs. 3. Evaluation of regeneration: a. Post-regeneration evaluation in schools, simulations, written tests, teaching practices in elementary / junior high schools & MI / MTs. b. Post practice evaluation: Written report and periodic monitoring.